Examining Criteria for Defining Persistent Post-concussion Symptoms in Children and Adolescents - Iverson, Grant L.; Karr, Justin E.; Maxwell, Bruce; Zafonte, Ross; Berkner, Paul D.; Cook, Nathan E. (Frontiers in Neurology, 2021)
Researchers operationalize persistent post-concussion symptoms in children and adolescents using varied definitions. Many pre-existing conditions, personal characteristics, and current health issues can affect symptom endorsement rates in the absence of, or in combination with, a recent concussion, and the use of varied definitions can lead to differences in conclusions about persistent symptoms and recovery across studies. This study examined how endorsement rates varied by 14 different operational definitions of persistent post-concussion symptoms for uninjured boys and girls with and without pre-existing or current health problems. This cross-sectional study included a large sample (age range: 11-18) of girls (n=21,923) and boys (n=26,556) without a recent concussion who completed the Post-Concussion Symptom Scale at preseason baseline. Endorsements rates varied substantially by definition, health history, and current health issues. The most lenient definition (i.e., a single mild symptom) was endorsed by most participants (54.5% of boys/65.3% of girls). A large portion of participants with pre-existing mental health problems (42.7% of boys /51.5% of girls), current moderate psychological distress (70.9% of boys /72.4% of girls), and insufficient sleep prior to testing (33.4% of boys /47.6% of girls) endorsed symptoms consistent with mild ICD-10 postconcussional syndrome; whereas participants with no current or prior health problems rarely met this definition (1.6% of boys /1.6% of girls). The results illustrate the tremendous variability in the case definitions of persistent symptoms and the importance of harmonizing definitions across future studies.